L’accès aux fonds contemporains des archives nationales de Tunisie : un état des lieux - Houda Ben Hamouda (L’Année du Maghreb)
Since the collapse of the authoritarian regime of Ben Ali, references to national history, particularly in the contemporary period are very present in the public debate in Tunisia and calling for re-readings of the past. This interest in history and the need to rethink it raises the question of access to sources. The recent opening of contemporary public records does not seem to arouse curiosity in the current transition period, except the police and court records and documents that may help to disqualify political opponents. The quick inventory of contemporary Tunisian national archives that we offer would promote the necessary renewal of the historiography of modern Tunisia.